Emotions and the Optimality of Unfair Tournaments - Matthias Kräkel (Sonderforschungsbereich/Transregio 15 - Governance and the Efficiency of Economic Systems (GESY), 2005)
We introduce a concept of emotions that emerge when workers compare their own performance with the performances of co-workers. Assuming heterogeneity among the workers the interplay of emotions and incentives is analyzed within the framework of rank-order tournaments which are frequently used in practice. Tournaments seem to be an appropriate starting point for this concept because the main idea of a tournament is inducing incentives by making workers compare themselves with their opponents. We differentiate between exogenous and endogenous tournament prizes and identify certain conditions under which the employer benefits from emotional workers. In this case, he clearly prefers unfair to fair tournaments. Furthermore, the concept of emotions is used to explain the puzzling findings on the oversupply of effort in experimental tournaments.
urn:nbn:de:bvb:19-epub-13503-3
Keywords: J3; M5; 330; anger; emotions; pride; tournaments